2013
DOI: 10.1080/0309877x.2011.645468
|View full text |Cite
|
Sign up to set email alerts
|

Mature student experiences in teacher education: widening participation in Greece and England

Abstract: In the context of a growing number of mature students entering higher education in Europe, this study breaks new ground in comparing the personal and professional identities of mature student teachers in Greece and England. Using an analytical model of student success by Zepke and Leach (2008), the research sought to identify the factors affecting the progress and development of 30 mature student teachers (15 in each country). It was found that individual motivation and prior experience were assets in the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 21 publications
(29 reference statements)
2
20
0
2
Order By: Relevance
“…Similarly, Waller, Mathers, Savidge, Flook, and Hamm (2017) acknowledged that knowledgeable students should conduct tutoring with valuable resources that would otherwise be less accessible and boost academic performance at the UAP level; thereby increasing access to Higher Education. Kaldi and Griffiths (2013) attributed performance and success to a range of institutional influences, one of which was support by tutors. Kaldi and Griffiths (2013) also affirmed that learning from tutors provides an additional positive influence on learning and student success.…”
Section: Scarcity Of Tutoring Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Waller, Mathers, Savidge, Flook, and Hamm (2017) acknowledged that knowledgeable students should conduct tutoring with valuable resources that would otherwise be less accessible and boost academic performance at the UAP level; thereby increasing access to Higher Education. Kaldi and Griffiths (2013) attributed performance and success to a range of institutional influences, one of which was support by tutors. Kaldi and Griffiths (2013) also affirmed that learning from tutors provides an additional positive influence on learning and student success.…”
Section: Scarcity Of Tutoring Supportmentioning
confidence: 99%
“…Kaldi and Griffiths (2013) attributed performance and success to a range of institutional influences, one of which was support by tutors. Kaldi and Griffiths (2013) also affirmed that learning from tutors provides an additional positive influence on learning and student success.…”
Section: Scarcity Of Tutoring Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Her children and husband also benefitted from the cultural experience of Ellie's study abroad semester. Ellie noted, though, that her children had to 'cope' with her being less available due to her enrolment, a sentiment shared by mature students in other studies (Kaldi & Griffiths, 2011;Tett, 2000).…”
Section: Analysis Of Ellie's Storymentioning
confidence: 99%
“…The academic aspects of university were not major issues for David, and were only part of the reason Rosie changed her pathway. Kaldi and Griffiths (2011) also noted that mature (postgraduate) teaching students in their study managed the academic demands of courses but many found school experiences challenging. Universities may put too much emphasis on the academic skill demands of universities when resourcing student support, when perhaps other elements may need more attention for some students (Benson et al, 2012).…”
Section: Transformative Opportunitiesmentioning
confidence: 99%